Association of Body Weight and Fat Mass with Pain Sensitivity and Pain Tolerance (P16-002-19). (13th June 2019) - Akter, Sharmin; Dawson, John; Quarles, William; Huang, Wei-Lin; Binks, Martin
Abstract: Objectives: Obesity is a risk factor for acute and chronic pain. Research on obesity and pain sensitivity (PS) and tolerance (PT) has produced mixed results. We examined the association of body weight (BW), fat mass (FM) and weight status (WS; BMI 18.5 – 24.9 or ≥25 kg/m 2 ) with pre- and post-exercise PS and PT to better understand these relationships. Methods: This was a cross-sectional analysis (N = 120, 18 - 60 years, BMI ≥18.5 kg/m 2 ) of data obtained during a single session. First, BW, FM were measured and BMI calculated. Dolorimetry measured PS and PT before and after a moderate exercise session (elliptical trainer; 2.5 – 3 mph, ≤42 mins.). Dolorimeter applied non-damaging pressure on the middle finger; PS is the pressure when the subject first reports pain, PT is the pressure when the subject is too uncomfortable to tolerate further. We performed multiple linear regression to determine the association of outcome variables (pre- and post- PS and PT and change of PS and PT) with predictor variables (BW, FM, and WS) using relevant covariates (age, sex). We conducted backwards stepwise model selection and reported the best models according to the Bayesian Information Criterion. Results: None of the full models explained > 9% of the outcome variation, across all outcomes. Pre- and post- PT were positively associated with BW ( r = .262, P = .003; r = .185, P = .047). The association of BW with pre- and post- PS, and changes in PS and PT were not significant. FM and age had no significant associations with outcome variables. The only linear models with significant predictors after backwards selection modeled pre-PT, and differed depending on whether or not BW was included directly or dichotomized as WS: The model with WS devolved to one with only FM and age, where higher FM is associated with more pre-PT (+51 gf/cm 2 per kg, P = .024) and men have more pre-PT than women (1296 gf/cm 2, P = .013). The model that instead began with BW devolved to one with only BW, where higher BW is associated with more pre-PT (+38 gf/cm 2 per kg, P = .004). Conclusions: People with higher BW had higher PT at baseline. However, pre-PS and changes in PS and PT following exertion were not significantly affected by our covariates of interest. Whether the observed relationship between BW and pre-PT is trying to capture FM and/or sex differences is unclear, as these are all strongly co-linear. Funding Sources: Texas Tech University.